The Correlation between Hemoglobin Level, Age, and Family History of Febrile Seizure with The Incidence of Febrile Seizure in Children - Istiqomah, Wimakrifah; Kartika Setyarini, Tri; Ratnaningrum, Kanti (Universitas Ahmad Dahlan, 2024)
Febrile seizure is a seizure that occur when the body temperature increases and is caused by an extracranial process. There are several risk factors of febrile seizure, including hemoglobin level,-age,-and family history of febrile seizure. The aim of this study was to analyze the relationship between hemoglobin level, age, and family history of febrile seizure with the incidence of febrile seizure in 6-60 months children in Fatimah-Hospital-of Mother-and-Child-Lamongan. This study used a case-control design through retrospective approach based on data of children’s medical records in Fatimah-Hospital Lamongan from January-November 2021. The sample was selected by consecutive sampling method. Data analysis were using the chi-square test and continued with multiple logistic regression tests. The sample of this study was 80 children, consist of each 40 children as case and control group. Most of the febrile seizure occured in children with a low hemoglobin level (85%), in age of 6-24 months (82,4%), and have a family history of febrile seizure (65%). The result of the bivariate analysis showed that there was significant correlation between hemoglobin level (p = 0,022), age (p = 0,015), and family history of febrile seizure (p = 0,000) with the incidence of febrile seizure. The result of the multivariate analysis showed that the most influential variable is family history of febrile seizure (OR=13,670). There was significant correlation between hemoglobin level,-age,-and family history of febrile seizure with the incidence of febrile seizure. Family history was the most influences factor for the incidence of febrile seizure.